A Physics-Based Compact DC Model for AOS TFTs Considering Effects of Active Layer Thickness Variation - Minxi Cai; Wei Zhong; Bei Liu; Piaorong Xu; Jing Cao (IEEE Journal of the Electron Devices Society)
A DC model is proposed for amorphous oxide semiconductor (AOS) thin-film transistors (TFTs) applicable to various active layer thicknesses. With the back surface potential and its coupling with the front surface potential being considered, an explicit potential solution is developed. Then, the analytical drain current and physical definition of threshold voltage are derived based on a non-chargesheet expression of free charge density. It is verified that in the previous models for AOS TFTs, typically ignoring the back surface potential and the active layer thickness effects could result in obvious deviations in the values of parameters during the characterization of DC performance, especially for scaled devices with low channel thicknesses. By comparing with numerical calculations and experimental data, this model is validated to be more suitable for AOS TFTs with decreased dimensions, which could give more realistic distributions of the density of states in the channel during parameter extraction.